A lithium ion full-tab stacked battery
Patent Information
- Application Number
- CN202521915087.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2035-09-05
AI Technical Summary
但具有成本较高,散热率较低的缺点
[0021]1、由于隔膜8沿极片长度方向依次包覆正极极片4和负极极片5,形成正极极片4-隔膜8-负极极片5-隔膜8的交替结构,正极极片4和负极极片5的全极耳沿极片宽度方向相反排布,能够缩短内部导热路径,使得热量分布更加均匀。
Smart Images

Figure CN224841860U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the field of battery technology, and in particular to a lithium-ion multi-tab stacked battery. Background Technology
[0002] The heat dissipation performance of lithium-ion batteries directly affects their safety, lifespan, energy efficiency, and operational stability. Currently, mainstream lithium-ion batteries include pouch cells encapsulated with aluminum-plastic film and prismatic aluminum-cased batteries. Cell manufacturing technologies primarily include winding and stacking. Pouch cells have poor thermal conductivity due to the aluminum-plastic film, relying mainly on internal electrode materials such as copper foil, aluminum foil, and electrolyte for heat conduction. External modules, such as thermally conductive adhesive fillers, liquid cooling plates, or air-cooling systems, are needed for auxiliary heat dissipation. Cells manufactured using winding technology suffer from severe heat accumulation in the central area, uneven interlayer contact, high thermal resistance, and relatively fewer tabs leading to higher resistance and more heat generation. In contrast, prismatic aluminum-cased batteries have the advantage of high thermal conductivity in the aluminum casing, allowing them to directly contact liquid cooling plates or air ducts for heat dissipation. In cells manufactured using the stacking process, the electrode sheets are stacked in parallel, shortening the internal heat conduction path, resulting in more uniform heat distribution. Furthermore, stacked cells have more tabs, lower resistance, and reduced localized heat generation. At the same time, the tabs, as components that come into direct contact with the battery cell, can also serve as heat conduction paths to dissipate the heat generated on the electrode plates.
[0003] Currently, the heat dissipation bottleneck of square aluminum-cased batteries is "large volume - high heat - weak thermal conductivity". There are problems such as long heat conduction paths, increased distance between the heat source inside the large-capacity cell and the casing, heat needing to pass through multiple interfaces such as electrodes, separators, and electrolytes, poor thermal conductivity of separator materials, and significant temperature gradients. Heat conduction perpendicular to the electrode direction is hindered by multiple layers, resulting in low heat dissipation efficiency and easy to trigger thermal runaway.
[0004] Patent application CN115000642A discloses a square stacked battery, including a combined cover plate, a stacked assembly, an insulating film, and an aluminum shell. The stacked assembly includes electrode groups, with positive and negative electrode tabs on both sides of the electrode groups. Electrode output connection components are mounted on both the positive and negative electrode tabs, and these components are bent. The combined cover plate includes a top cover plate with multiple electrode assembly terminals mounted on it. An insulating thrust member is located on one side of the top cover plate near the stacked assembly. The electrode output connection components include electrode output terminals and electrode connecting pieces connected to these terminals. This application, through its battery structure design, allows for welding after sealing, ensuring high-current output performance. It also expands the capacity of the square battery through a parallel structure of multiple stacked assemblies, prevents metal fumes from entering the battery, improves reliability, reduces the probability of safety accidents, and increases the battery's volumetric energy density. However, it suffers from low heat dissipation efficiency.
[0005] Patent application CN215644689U discloses a horizontally stacked battery cover plate and its lithium battery. Both the positive and negative cover plates include rivets, terminals, insulating pads, a cover plate body, rivet fixing blocks, and adapter plates. Injection holes and safety valves are respectively located on the positive and negative cover plates. The horizontally stacked battery includes a positive cover plate, an aluminum shell, a battery cell, and a negative cover plate. The aluminum shell has a hollow structure at both ends. The positive and negative cover plates are welded to both ends of the aluminum shell. The addition of rivet structures to the terminals on the cover plates prevents short circuits and fires during fast charging of the lithium battery. The positive and negative terminals in this application are located at both ends of the battery, increasing the current-carrying area and improving battery capacity. The safety valve is a steel sheet welded with sealing nails, and the steel sheet manufacturing process is relatively simple. The cover plate body adopts a stepped structure, allowing for full-side welding, effectively improving battery safety performance, ensuring welding efficiency, and avoiding incomplete welds. However, it has the disadvantages of complex structure and difficulty in implementation.
[0006] Patent application CN220021219U discloses a square lithium-ion battery stacked core pack assembly and a stacked battery, including a core pack body and a first adhesive strip attached to the outer surface of the thinned area of the core pack body. The first adhesive strip is used to compensate for the thickness of the thinned area. This core pack assembly structure directly compensates for the thickness of the core pack body. The stacked battery includes a core pack assembly and an aluminum shell. During the manufacturing of the stacked battery, the thickness compensation is completed before the core pack assembly is placed into the aluminum shell, eliminating the need for additional aerogel treatment on the outside of the aluminum shell. On the one hand, the adhesive strip method has lower production costs and higher efficiency. On the other hand, under the condition of a fixed aluminum shell space, it does not cause an additional increase in the volume of the stacked battery, increasing the space utilization rate of the module assembly, improving the volumetric energy density of the module, and facilitating its promotion. However, it has the disadvantages of higher cost and lower heat dissipation.
[0007] In summary, existing square aluminum-cased stacked batteries suffer from limitations in material and structural heat dissipation performance, leading to issues such as thermal runaway risk, uneven temperature distribution, thermal conductivity bottlenecks, and the complexity and cost of thermal management systems, which urgently need to be addressed. Summary of the Invention
[0008] In order to overcome the shortcomings of the prior art, the purpose of this utility model is to provide a lithium-ion full-tab stacked battery. The full-tab design conducts the heat generated inside the cell to the shell from the direction parallel to the electrode through the large area of the full-tab structure. Through ultrasonic welding and stacking structure, the internal heat conduction path can be shortened, which can effectively improve the heat transfer efficiency and save the volume and cost of heat dissipation equipment.
[0009] To achieve the above objectives, the technical solution adopted by this utility model is as follows:
[0010] A lithium-ion multi-tab stacked battery includes a cell 19, in which a positive electrode 4 and a negative electrode 5 are disposed. A separator 8 sequentially covers the positive electrode 4 and the negative electrode 5 along the length of the electrode, forming an alternating structure of positive electrode 4-separator 8-negative electrode 5-separator 8. The multi-tabs 1 of the positive electrode 4 and the negative electrode 5 are arranged in opposite directions along the width of the electrode. The positive multi-tabs 12 are concentrated on one side of the cell 19, and the negative multi-tabs 13 are concentrated on the other side of the cell 19, forming a multi-tab group arranged on both sides of the cell 19.
[0011] The battery cell 19 is provided with a Mylar film 9 on its outside, and the Mylar film 9 is provided with a plurality of insulating film holes 14 on the short side of the battery cell 19.
[0012] The battery cell 19 is also provided with a positive electrode adapter block 10 and a negative electrode adapter block 11 on its exterior. The positive electrode adapter block 10 and the negative electrode adapter block 11 are respectively provided with an embedding groove. The positive electrode tab 12 is fixedly connected to the positive electrode adapter block 10 through the embedding groove on the positive electrode adapter block 10, and the negative electrode tab 13 is fixedly connected to the negative electrode adapter block 11 through the embedding groove on the negative electrode adapter block 11. The width of the embedding groove is 1.1-1.3 times the thickness of the tab 1.
[0013] The positive electrode adapter block 10 and the negative electrode adapter block 11 are provided with an electrode block insulating plastic bracket 18 on the side with the embedding groove.
[0014] After the positive electrode 4 and negative electrode 5 are coated, during the electrode cutting process, a continuous blank area without slurry is retained on one side of the long side of the electrode as the full tab 1 of the electrode.
[0015] The length of the full electrode tab 1 is equal to the length of the positive electrode 4 and the negative electrode 5, and the width is 8%-12% of the overall width of the electrode.
[0016] The diaphragm 8 completely covers the active material area of the electrode, and the edge of the diaphragm 8 is wider than the edges of the positive electrode 4 and the negative electrode 5.
[0017] The positive electrode tab 12 and the negative electrode tab 13 are fixed by ultrasonic welding.
[0018] The number of lamination layers of the battery cell 19 is 100-150.
[0019] The positive electrode tab 12 is made of aluminum foil, the negative electrode tab 13 is made of copper foil, and the positive electrode adapter 10 and the negative electrode adapter 11 are made of metal and are connected to the battery casing 15 to serve as battery electrodes.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. Since the diaphragm 8 sequentially covers the positive electrode 4 and the negative electrode 5 along the length of the electrode, forming an alternating structure of positive electrode 4-diaphragm 8-negative electrode 5-diaphragm 8, and the tabs of the positive electrode 4 and the negative electrode 5 are arranged in opposite directions along the width of the electrode, the internal heat conduction path can be shortened, making the heat distribution more uniform.
[0022] 2. Since the core 19 is provided with a Mylar film 9, and the Mylar film 9 is provided with several insulating film holes 14 on the short side of the core 19 to facilitate the subsequent penetration of electrolyte, the Mylar film 9 provided on the outside of the core 19 can provide a physical buffer for the core 19 and the battery casing 15.
[0023] 3. Since both the positive electrode 4 and the negative electrode 5 adopt the full tab 1, the full tab 1 does not need to be die-cut. The entire blank area is used as the tab, making its area much larger than that of the conventional tab after die-cutting. The heat conduction effect of the enlarged tab structure is used to improve the heat dissipation efficiency in the direction parallel to the electrode and reduce the cost of the heat dissipation mechanism.
[0024] In summary, this utility model adopts a stacked structure, which can shorten the internal heat conduction path and make the heat distribution more uniform. At the same time, it adopts a large-area full-tab structure, which improves the heat conduction effect by increasing the area of the tab structure, thereby improving the heat dissipation efficiency parallel to the electrode direction and reducing the cost of the heat dissipation mechanism. It has the characteristics of improving heat dissipation efficiency and reducing costs. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the positive electrode coating region 2 of the total electrode tab 1 of this utility model.
[0026] Figure 2 This is a schematic diagram of the negative electrode coating area 3 of the total electrode tab 1 of this utility model.
[0027] Figure 3 This is a schematic diagram of the stacked plates of this utility model.
[0028] Figure 4 This is a schematic diagram of the Mylar membrane 9 of this utility model.
[0029] Figure 5 This is an assembly diagram of the present invention.
[0030] Figure 6 This is a perspective view of the adapter block 10 of this utility model.
[0031] Figure 7 This is a front view of the adapter block 10 of this utility model.
[0032] Figure 8 This is a top view of the adapter block 10 of this utility model.
[0033] Figure 9 This is a side view of the adapter block 10 of this utility model.
[0034] Figure 10 This is a cross-sectional view of the present invention.
[0035] The components are: 1. All tabs; 2. Positive electrode coating area; 3. Negative electrode coating area; 4. Positive electrode sheet; 5. Negative electrode sheet; 6. Positive electrode tab; 7. Negative electrode tab; 8. Separator; 9. Mylar membrane; 10. Positive electrode adapter block; 11. Negative electrode adapter block; 12. Positive electrode all tabs; 13. Negative electrode all tabs; 14. Insulating film pores; 15. Battery casing; 16. Insulating rubber ring; 17. Electrolyte filling hole; 18. Insulating plastic bracket; 19. Battery cell; 20. System fan. Detailed Implementation
[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention.
[0037] Reference Figure 1 , Figure 2 and Figure 3 A lithium-ion multi-tab stacked battery includes a cell 19, in which a positive electrode 4 and a negative electrode 5 are disposed. After the positive electrode 4 and the negative electrode 5 are coated, during the electrode cutting process, a continuous blank area without slurry is retained on one side of the long side of the electrode as the multi-tab 1 of the electrode.
[0038] Reference Figure 3 The diaphragm 8 sequentially covers the positive electrode 4 and the negative electrode 5 along the length of the electrode, forming an alternating structure of positive electrode 4-diaphragm 8-negative electrode 5-diaphragm 8. The tabs 1 of the positive electrode 4 and the negative electrode 5 are arranged in opposite directions along the width of the electrode. The positive tabs 12 are concentrated on one side of the cell 19, and the negative tabs 13 are concentrated on the other side of the cell 19, forming a group of tabs arranged on both sides of the cell 19.
[0039] Reference Figure 4 and Figure 10 The battery cell 19 is externally covered with a Mylar film 9. The Mylar film 9 has several insulating membrane holes 14 on the short side of the battery cell 19 to facilitate the subsequent penetration of electrolyte; or the Mylar film 9 is wound in sections at intervals along the short side of the battery cell 19, leaving space for electrolyte penetration. The battery cell 19 is first shaped using a hot pressing process to eliminate interlayer gaps and improve the adhesion between the electrode and the separator 8 to reduce internal resistance; after hot pressing, a cold pressing process is used to maintain the dense structure of the battery cell 19, and the opening of the battery cell 19 is sealed with an insulating rubber ring 16 to ensure the dimensional stability of the battery cell 19.
[0040] Reference Figure 5 After the battery cell 19 is shaped, the edges of the full electrode tabs on both sides of the battery cell 19 are pinched together, and the positive electrode full electrode tab 12 and the negative electrode full electrode tab 13 on the same side are pre-welded using ultrasonic welding process to form an integral full electrode tab 1, so as to gather and press the full electrode tab 1 to prepare for welding the full electrode tab 1 to the adapter plate.
[0041] Reference Figure 5 The battery cell 19 is externally fitted with a battery casing 15. The battery casing 15 is a square aluminum shell, precision-machined from high-strength square aluminum alloy. A gap of 0.5-1mm is reserved between the inner surface of the battery casing 15 and the battery cell. The battery casing 15 has a four-sided structure, covering the four sides of the battery cell 19 without tabs. The internal dimensions of the battery casing 15 match the external dimensions of the battery cell 19, ensuring that the battery cell 19 can be smoothly embedded in the casing 15 with the smallest possible gap between the battery cell 19 and the casing 15. The wound Mylar film 9 acts as a physical buffer between the battery cell 19 and the battery casing 15.
[0042] Reference Figure 10 The battery cell 19 is also provided with a positive electrode adapter block 10 and a negative electrode adapter block 11. The positive electrode adapter block 10 and the negative electrode adapter block 11 are respectively provided with an embedding groove with a width of 1.1-1.3 times the thickness of the full electrode tab. The positive electrode full electrode tab 12 is fixedly connected to the positive electrode adapter block 10 through the embedding groove on the positive electrode adapter block 10, and the negative electrode full electrode tab 13 is fixedly connected to the negative electrode adapter block 11 through the embedding groove on the negative electrode adapter block 11. The full electrode tab is fitted and connected to the adapter block by ultrasonic welding to achieve precise matching. On the side of the positive electrode adapter block 10 and the negative electrode adapter block 11 with the embedding groove, an electrode block insulating plastic bracket 18 is also provided to fix the relative position of the adapter block and the battery casing 15 and to fix the battery cell 19.
[0043] Both the positive electrode 5 and the negative electrode 6 adopt full tabs 1. The full tabs 1 do not require die-cutting. The entire blank area is used as the tabs, and the area of the structure is larger than that of conventionally die-cut tabs. By increasing the area of the tab structure, the heat conduction effect is improved, thereby improving the heat dissipation efficiency parallel to the electrode direction and reducing the cost of the heat dissipation mechanism.
[0044] The length of the full electrode tab 1 is equal to the length of the positive electrode 4 and the negative electrode 5, and the width is 8%-12% of the overall width of the electrode, preferably 10%.
[0045] The diaphragm 8 completely covers the active material area of the electrode, and the edge of the diaphragm 8 is wider than the edges of the positive electrode 4 and the negative electrode 5 to avoid short circuit between the positive electrode 5 and the negative electrode 6.
[0046] The cell 19 has 100-150 layers, preferably 120-140 layers, to achieve a balance between high energy density and structural stability. It can also include A and B cells, which is beneficial for the design of large-capacity energy storage batteries.
[0047] Reference Figure 5 The battery casing 15 is also provided with an injection port 17. The injection port 17 is located on the short side of the battery casing 15, and is welded with glue nails after the electrolyte is filled in. The injection port 17 can be provided on both short sides of the battery casing 15. When filling the electrolyte, it is poured from one side and a vacuum is drawn from the other side to allow the electrolyte to be quickly injected and wet the battery cell 19. Alternatively, the injection port 17 can be provided only on one short side of the battery casing 15. The electrolyte is injected from one side and gradually penetrates into the interior of the battery cell 19.
[0048] Reference Figure 10 A fan 20 can be installed on the outside of the battery to blow out the heat generated inside the cell 19 that is transferred to the outer surfaces of the positive electrode adapter 10 and the negative electrode adapter 11, so that the battery heat dissipation relies more on the internal structure and materials, and reduces the dependence on the design of external heat dissipation modules.
[0049] Meanwhile, by setting up full tabs 1, positive electrode adapter 10 and negative electrode adapter 11 on the long side to replace the cover plate and directly contact the air, the heat dissipation area is increased, thereby increasing the electrode width, which in turn increases the area of the active material coating and the thickness of the stack, which is beneficial for making large-capacity batteries.
[0050] The manufacturing process of this utility model battery is as follows:
[0051] Step S1: Using LFP (LiFePO4) as the positive electrode slurry, double-sided coating is completed on an aluminum foil with a thickness of 10-20 μm; using graphite as the negative electrode slurry, the same coating process is applied to a copper foil with a thickness of 10-20 μm; during the coating process, the surface density and thickness consistency of the slurry are strictly controlled to ensure stable electrode performance; after coating, a precisely controlled rolling process is required for compaction to obtain ideal electrode density and porosity;
[0052] Step S2: Using a precision cutting device, a continuous blank area without slurry with a width of 10% of the total width of the electrode is retained on one side of the long side along the length direction of the electrode. The length of this blank area is consistent with the total length of the electrode, thereby forming a complete full-tab structure.
[0053] Step S3: Using automated equipment, the positive electrode 4, separator 8, and negative electrode 5 are precisely stacked in a predetermined order. The separator 8 completely covers the coating area of the electrode along its length, and the edge of the separator 8 must extend 1-2 mm beyond the coating edge to ensure sufficient insulation. During stacking, the positive electrode tab 6 and the negative electrode tab 7 are arranged in opposite directions, i.e., the positive electrode tab 6 is arranged to the left and the negative electrode tab 7 is arranged to the right. The number of stacked layers is controlled within the range of 50-100 layers, ultimately forming a regular structure with the positive and negative electrode tab groups concentrated on both sides of the cell 19. After stacking, the cell 19 is wrapped with Mylar film 9.
[0054] Step S4: During electrode tab welding and encapsulation, firstly, use a high-temperature resistant polyimide insulating ring 16 to tightly wrap the open end of the cell 19 to prevent short circuits. Then, use high-precision ultrasonic welding equipment to weld the electrode tabs on the same side. The welding parameters for the positive aluminum electrode tab are a frequency of 20-30kHz and a pressure of 300-400N, while the parameters for the negative copper electrode tab are a frequency of 15-25kHz and a pressure of 400-500N, to ensure that the contact resistance between the electrodes is strictly controlled below 0.5mΩ.
[0055] Step S5: Finally, apply 10-20MPa pressure at 80-100℃ and hold for 5-10 minutes for hot pressing to eliminate interlayer gaps. Then, perform cold pressing at 2-5MPa pressure at room temperature for 3-5 minutes to ensure the long-term stability of the cell structure.
[0056] The thickness parameters of each functional layer are as follows: the positive electrode 4 is composed of a 15μm aluminum foil substrate and a 70-150μm thick LFP active coating; the negative electrode 5 is composed of a 10μm copper foil substrate and an 80-120μm graphite coating; the separator 8 has a thickness of 12-25μm. The cell 19 adopts a 50-100 layer stacked structure, and its total thickness can be calculated by the formula T≈1.03N×(Tcathode+Tanode+2×Tsep), where 1.03 is a correction factor considering manufacturing process factors.
[0057] The total thickness Ttab of the entire tab 1 is determined by the product of the single-layer tab thickness t and the number of stacked layers N. The total width of the cell 19 consists of three parts: the width of the electrode coating area and the sum of the widths of the positive and negative tabs. The battery casing 15 is designed with an inner wall length of 203-303mm, a width of 103-203mm, and a casing thickness of 20-40mm, matching the dimensions of the cell 19.
[0058] This invention ensures the coordination of the battery structure and its manufacturing feasibility by precisely controlling the dimensional parameters of each component. The thickness correction factor of 1.03, derived from accumulated practical production experience, is used to compensate for tolerance effects during the stacking process. The setting of each dimensional parameter considers both material properties and production process requirements, achieving a balance between performance and manufacturability.
[0059] This invention achieves a comprehensive improvement in battery performance through systematic process design and precise parameter control.
[0060] Example 1
[0061] For high-energy-density all-tab batteries, this embodiment uses a lithium iron phosphate (LFP) cathode system. The cathode aluminum foil thickness is 15μm, and LFP active material is coated on both sides, with the coating surface density controlled at 25mg / cm³. 2 After rolling, the total thickness of the positive electrode sheet is 150 μm. The negative electrode uses 10 μm copper foil coated with artificial graphite material, with an areal density of 13 mg / cm³. 2 The compacted negative electrode sheet has a thickness of 120μm. A 16μm thick PE separator is used, with 80 layers stacked. The width of all tabs is designed to be 15mm, and the total cell thickness is calculated to be 28.6mm (including a correction factor of 1.03). The positive aluminum tabs are welded using 25kHz / 350N parameters, and the negative copper tabs are welded using 20kHz / 450N parameters. The casing dimensions are 283×133×32mm, integrating 4mm high heat dissipation fins. Testing shows that the battery achieves a volumetric energy density of 420Wh / L, a capacity retention of 91.2% after 1000 5C cycles, and a temperature rise controlled within 18℃.
[0062] Example 2
[0063] For high-rate-density all-tab batteries, this embodiment uses NCM811 cathode material, reduces the cathode aluminum foil thickness to 12μm, and lowers the coating surface density to 20mg / cm². 2 To improve ion conduction efficiency, the negative electrode uses an 8μm ultra-thin copper foil, paired with fast-charging graphite material. The tab width is increased to 18mm to reduce current density, and the number of stacked layers is optimized to 60 layers. The welding process is adjusted to 28kHz / 380N (positive electrode) and 22kHz / 480N (negative electrode). A specially designed 3mm dense heat dissipation fin (5mm spacing) is incorporated. Tests show that the battery retains 95% of its discharge capacity at 10C, with a peak temperature rise of only 22℃, and can achieve 80% SOC in 30 minutes of fast charging, meeting the fast-charging requirements of electric vehicles.
[0064] Example 3
[0065] For consumer electronics applications, this embodiment employs an ultra-thin design. The positive electrode uses 10μm aluminum foil, with the LFP coating thickness controlled at 70μm; the negative electrode uses 6μm copper foil, with a graphite layer thickness of 80μm. A 12μm ceramic-coated separator is selected, with 50 stacked layers. The tab width is reduced to 10mm, and the overall cell thickness is only 12.1mm. The casing thickness is reduced to 20mm, and the fin height is reduced to 3mm. By optimizing welding parameters (30kHz / 320N positive electrode, 25kHz / 420N negative electrode), a tab resistance of 0.38mΩ is achieved. This battery achieves an energy density of 300Wh / L within a 3mm thickness tolerance and a capacity retention of 93.5% after 2000 cycles at 0.5C.
[0066] Comparative Example
[0067] The same LFP positive and graphite negative electrode materials as in this application were used, but a conventional single-tab design was employed: the tab width was 5 mm, with leads extended only at one end. The number of laminated layers was 80, and other process parameters remained consistent with Example 1. Test results showed that: 1. The temperature rise at the tab reached 35°C at 5C discharge, 94% higher than the full-tab design; 2. The tab welding resistance reached 1.2 mΩ, 2.4 times that of the full-tab structure; 3. After 800 cycles at 3C, significant aging occurred at the tab connection, with a capacity retention of only 82%. This comparison demonstrates the significant advantages of the full-tab design in terms of heat dissipation performance, interface resistance, and cycle life.
[0068] The specific embodiments of the present invention have been described above by way of example. However, the scope of protection of the present invention is not limited to the above exemplary embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A lithium-ion multi-tab stacked battery, comprising a cell (19), characterized in that, The cell (19) is provided with a positive electrode plate (4) and a negative electrode plate (5). The separator (8) covers the positive electrode plate (4) and the negative electrode plate (5) in sequence along the length of the electrode plate, forming an alternating structure of positive electrode plate (4) - separator (8) - negative electrode plate (5) - separator (8). The tabs (1) of the positive electrode plate (4) and the negative electrode plate (5) are arranged in opposite directions along the width of the electrode plate. The positive tabs (12) are concentrated on one side of the cell (19), and the negative tabs (13) are concentrated on the other side of the cell (19), forming a group of tabs on both sides of the cell (19).
2. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, Mylar film (9) is provided on the outside of the battery cell (19), and several insulating film holes (14) are provided on the short side of the battery cell (19).
3. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, The cell (19) is also provided with a positive electrode adapter block (10) and a negative electrode adapter block (11). The positive electrode adapter block (10) and the negative electrode adapter block (11) are respectively provided with an embedding groove. The positive electrode tab (12) is fixedly connected to the positive electrode adapter block (10) through the embedding groove on the positive electrode adapter block (10). The negative electrode tab (13) is fixedly connected to the negative electrode adapter block (11) through the embedding groove on the negative electrode adapter block (11). The width of the embedding groove is 1.1-1.3 times the thickness of the tab (1).
4. A lithium-ion multi-tab stacked battery according to claim 3, characterized in that, The positive electrode adapter block (10) and the negative electrode adapter block (11) are provided with an insulating plastic bracket (18) on the side with the embedded groove.
5. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, After the positive electrode (4) and negative electrode (5) are coated, during the electrode cutting process, a continuous blank area without slurry is retained on one side of the long side of the electrode as the full electrode tab (1).
6. A lithium-ion multi-tab stacked battery according to claim 1 or 5, characterized in that, The length of the full electrode tab (1) is equal to the length of the positive electrode plate (4) and the negative electrode plate (5), and the width is 8%-12% of the overall width of the electrode plate.
7. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, The diaphragm (8) completely covers the active material area of the electrode, and the edge of the diaphragm (8) is wider than the edges of the positive electrode (4) and the negative electrode (5).
8. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, The positive electrode tab (12) and the negative electrode tab (13) are fixed by ultrasonic welding.
9. A lithium-ion multi-tab stacked battery according to claim 1, characterized in that, The number of laminations in the battery cell (19) is 100-150.
10. A lithium-ion multi-tab stacked battery according to claim 3, characterized in that, The positive electrode tab (12) is made of aluminum foil, the negative electrode tab (13) is made of copper foil, and the positive electrode adapter (10) and the negative electrode adapter (11) are made of metal. They are connected to the battery casing (15) and serve as battery electrodes.
Citation Information
Patent Citations
Square laminated battery
CN115000642A
Square lithium battery laminated core package assembly and laminated battery
CN220021219U